Synthesis and Characterization of Titanium Dioxide Nano Particles and their Application in Environmental Remediation of Textile Dyes - Termazi, Naima; Abbas, Farhat; Hussain Bukhari, Iftikhar; Mahmood Bhatti, Tariq; Riaz, Muhammad; Aftab Rafiq, Muhammad; M. Khan, Qaiser; Noreen, Mnaza; Gull, Yasmeen (Asian Journal of Chemistry, 2013)
The waste water of different textile industries when enter to a water body it impairs that water and inhibits sunlight to reach at the bottom thus affecting flora and also due to process of bioaccumulation and biomagnifications, it can harm fauna and ultimately humans. Moreover this waste water comes into contact with people when this polluted water is used for washing of different edibles as fruits and vegetables. In this study we synthesized titanium dioxide nanoparticles through co-precipitation method and tested their effect on remediation of different dyes. For this purpose we took reactive azo dyes from a manufacturing company and make synthetic effluents. Samples were prepared in accordance to the standard procedures and protocols.